2015
DOI: 10.2174/1874609809666151130220343
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Sleep Disruption and Reduction in the Circadian Rhythm of Urine Output: Contribution to Nocturia?

Abstract: Aging is associated with a marked increase in sleep complaints, and one factor causing sleep disruption is waking to void (nocturia). Urological surveys have found that few young adults report nocturia symptoms, but about half of those in their 60’s and nearly 80% of older age groups are affected. Sleep surveys have found nocturia is a major cause of sleep disruption, with a majority of older adults with sleep disruption citing the need to void as the cause of their awakening. While much of the urological lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 141 publications
0
20
0
1
Order By: Relevance
“…In simple terms, longer sleep times may be associated with a higher likelihood of waking up and voiding. Moreover, excessive sleep duration might interrupt circadian rhythms, which regulate urine output via diuretic and anti-diuretic hormones and other clock gene expressions 33 . On the other hands, nocturia could cause sleep disturbances and thereby prolong the total required sleep duration 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In simple terms, longer sleep times may be associated with a higher likelihood of waking up and voiding. Moreover, excessive sleep duration might interrupt circadian rhythms, which regulate urine output via diuretic and anti-diuretic hormones and other clock gene expressions 33 . On the other hands, nocturia could cause sleep disturbances and thereby prolong the total required sleep duration 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The International Continence Society defines nocturia as "the complaint that the individual has to wake at night one or more times to void" (van Kerrebroeck et al, 2002). The prevalence of nocturia in community-dwelling males and females >60 years of age is more than 50%, increasing greatly after age 65 years (Duffy et al, 2016;Jolleys et al, 1994;Lose et al, 2001;Lundgren, 2004). Indeed,~70% of healthy elderly adults experience nocturia, with 40% regularly experiencing ≥2 micturations during the sleep span.…”
Section: Nocturiamentioning
confidence: 99%
“…Intriguingly, we found that the proportion of RS was not highest in subjects with bilateral SHL at 4000 Hz in the oldest group, aged 70–79 years (Additional file 2 : Figure S1). One plausible explanation is that the association between SHL and RS may be modified by age-related insomnia [ 29 , 30 ] and common complications, such as urinary tract symptoms [ 16 , 31 ].…”
Section: Discussionmentioning
confidence: 99%